Binding to collagen by Yersinia enterocolitica and Yersinia pseudotuberculosis: evidence for yopA-mediated and chromosomally encoded mechanisms. - Emödy, L (1989)
Binding of Yersinia enterocolitica and Yersinia pseudotuberculosis strains to type I, II, and IV collagens has been studied. Wild-type strains which harbored the 40- to 50-megadalton virulence plasmid specifically bound all three types of collagen. Curing of the virulence plasmid or Tn5 insertion in the yopA gene encoding the temperature-inducible outer membrane protein YOP1 abolished the binding of all three collagen types to Y. enterocolitica and type I and II collagens to Y. pseudotuberculosis. Full binding capacity was restored by introduction of the yopA gene into nonbinding Yersinia strains. Binding of type I, II, and IV collagens was expressed in Escherichia coli constructs harboring the yopA gene of either Y. enterocolitica or Y. pseudotuberculosis. The interaction of bacterial cells with type I collagen could be blocked by nonradiolabeled native collagens or denatured collagen but not with other serum and connective-tissue proteins. Unlabeled collagen could not displace bound radiolabeled collagen. The binding was inhibited by YOP1-specific polyclonal antibodies, in contrast to normal rabbit serum. The interaction was rapid and was quite resistant to heat treatment, to proteolytic enzymes, to various pHs in both acidic and alkaline ranges, and to the chaotropic agent urea. We propose that this newly identified interaction may be involved both in the first steps of the pathogenesis and in the complications of Yersinia infections affecting connective tissue.